FINANCIAL INDEPENDENCE AS THE BASIS FOR THE TERMINATION OF A FATHER’S CHILD SUPPORT OBLIGATION: AN ANALYSIS OF PROTECTIONS FOR CHILDREN WITH DISABILITIES - Wike Sundari; Faisar Ananda (Al-Usrah : Jurnal Al Ahwal As Syakhsiyah, 2026)
This study investigates the legal framework of financial independence as a criterion for ending a father's duty to support his children, through the lenses of Islamic law and Indonesian positive law, and evaluates the sufficiency of this concept in safeguarding the rights of children, especially those with disabilities. The used research approach is normative legal research, which focuses on the examination of legal norms within legislation, doctrine, and other pertinent legal documents. The methodologies used consist of the statutory approach, the conceptual approach, and the comparative approach. The sources of legal materials include fundamental legal resources such as legislation and Islamic law sources (the Qur'an, Hadith, and scholarly views), along with secondary legal materials including books, academic journals, essays, and pertinent expert opinions. Data analysis was performed qualitatively using descriptive-analytical techniques. The study's findings reveal that neither Islamic law nor Indonesian positive law establishes a definitive age restriction for the cessation of assistance; instead, it is contingent upon the child's economic capacity for independent living. In Islamic jurisprudence, this is shown in the principles of al-kasb and al-i‘timād ‘ala al-nafs, but in Indonesian law, it is encapsulated in the expression “able to stand alone” as articulated in Article 45 paragraph (2) of the Marriage Law. Nonetheless, the notion of financial freedom cannot be universally applied, since not all children possess the same capacity to attain economic autonomy, particularly those with impairments who face enduring limits. Consequently, this idea must be comprehended with flexibility and contextuality, while maintaining a focus on the principles of justice and the safeguarding of children's rights.